(untitled) (Boletin Médico de Postgrado, 2024)
A systematic review of forty clinical cases was carried out in order to perform a clinical, epidemiological and microbiological characterization of an outbreak of Gram-negative Serratia marcescens bacteria occurred during the period January-December 2022 in the Hospital Universitario Pediatrico Dr. Agustin Zubillaga in the city of Barquisimeto, Lara State. There was a predominance of male sex (72.5%) with the Intensive Care Unit presenting the highest number of cases (44.7%) and the most affected age group was infants (44.7%). The most frequent clinical manifestation was sepsis (78%). The most frequent associated pathology was perinatal asphyxia (26.2%) and mortality was 27.5%. Sensitivity to amikacin and levofloxacin was found in 57.6% of the samples. An enterobacterial strain phenotypically belonging to the multidrug-resistant Serratia marcescens species with carbapenemase enzyme production and sensitive to levofloxacin and amikacin was isolated from the ventilator tubulations in the emergency area. Phenotypic and genetic certification was requested to the National Institute of Hygiene which reported Serratia marcescens producing carbapenemase type NDM and β-lactamase extended spectrum enzyme (BLEE) type TEM.